Accepting automated news as “low-quality” journalism - Olsen, Gunhild Ring (Journalistica, 2021)
This ethnographic case study explores how developers, editors, and reporters in two Norwegian newsrooms evaluate automated news and which logics underlie their assessments. Despite automation being described as the most disruptive data-centric practice of journalism, the observations and in-depth interviews show that all three groups define automated texts as journalism. At the same time, they characterize automated news as simplistic, lacking creativity and a critical approach, and argue that today’s machine-written texts are incapable of fulfilling central professional ideals such as critical scrutiny and advocating on behalf of the citizenry. Accepting automated news as journalism while simultaneously stressing its low quality shows a growing gap between what the newsroom groups are willing to accept because of organizational demands and what they ideally want journalism to be. The conflicting assessments may indicate financial motives gaining ground within Nordic media companies.